Neuropilin-2 mediates lymphangiogenesis of colorectal carcinoma via a VEGFC/VEGFR3 independent signaling. Issue 2 (28th March 2015) - Ou, Juan-Juan; Wei, Xing; Peng, Yuan; Zha, Lin; Zhou, Rong-Bin; Shi, Hang; Zhou, Qi; Liang, Hou-Jie
Highlights NRP2 expression levels of LECs are significantly correlated with the density of tumor lymphatic vessels in CRC. Activation of NRP2 in LECs substantially increases their migration, sprouting, and tubulogenesis capacity. NRP2 activation promotes CRC lymphangiogenesis via activating integrinα9β1/FAK/Erk signaling independent of VEGF pathway. NRP2 is a potential therapeutic target in preventing lymphatic metastasis of CRCs.